Prevalence, Bacterial Load, and Antimicrobial Resistance of Salmonella Serovars Isolated From Retail Meat and Meat Products in China - Yang, Xiaojuan; Wu, Qingping; Zhang, Jumei; Huang, Jiahui; Chen, Ling; Wu, Shi; Zeng, Haiyan; Wang, Juan; Chen, Moutong; Wu, Haoming; Gu, Qihui; Wei, Xianhu (Frontiers in Microbiology, 2019)
Salmonella remains the leading cause of reported bacterial foodborne disease in China. Meat products obtained from livestock are recognized as one of the major sources of human salmonellosis; however, there is a lack of comprehensive, quantitative data concerning Salmonella contamination of these foods. Therefore, the objectives of this study were to investigate the prevalence, bacterial load, and antimicrobial resistance profiles of various Salmonella serovars in retail meat across the whole of China. Between July 2011 and June 2016, a total of 807 retail meat product samples were collected from 39 provincial capital cities in China. Overall, 159 (19.7%) samples tested positive for Salmonella. The highest contamination rate occurred in pork (37.3%, n = 287), followed by beef (16.1%, n = 161), mutton (10.9%, n = 92), dumplings (6.6%, n = 212), and smoked pork (3.6%, n = 55). Most probable number (MPN) analysis revealed that contamination was mainly in the range of 0.3–10 MPN/g among those samples testing positive using this method (n = 83), with eight samples exceeding 110 MPN/g. Among the 456 Salmonella enterica subsp. enterica isolates obtained in this study, 29 serovars and 33 multilocus sequence typing patterns were identified, with serovars Derby, Typhimurium, London, Rissen, 1,4,[5],12:i:-, Weltevreden, and Enteritidis being the most prevalent. Among the 218 non-duplicate isolates, 181 (83.0%) were resistant to at least one class of antimicrobials and 128 (58.7%) were resistant to at least three classes. High rates of resistance were observed for tetracycline (65.6%), ampicillin (45.4%), trimethoprim-sulfamethoxazole (40.8%), streptomycin (40.4%), and nalidixic acid (35.8%), with the seven most prevalent serovars, except Weltevreden, showing higher rates of resistance and multidrug resistance compared with the less dominant serovars. Of note, all S. Indiana isolates exhibited resistance to extended-spectrum cephalosporins (including ceftriaxone and cefepime), ciproﬂoxacin, and multiple other classes of antibiotics. Further, two S. 1,4,[5],12:i:- isolates showed resistance to imipenem. This study provides systematic and comprehensive data on the prevalence and antimicrobial resistance profiles of various Salmonella serovars isolated from livestock-derived meat products in China, indicating their potential risk to public health.